2016
DOI: 10.1590/s0102-865020160020000002
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted ovariohysterectomy in domestic cats (Felis catus, Linnaeus, 1758) using two access portals

Abstract: PURPOSE:To describe video-assisted ovariohysterectomy (OHE) with two portals access in adult intact queens. METHODS:Fifty-two females cats were used. A 4 mm cannula was positioned in the abdomen through an incision close to the umbilicus (first portal), and a pneumoperitoneum was established. A second portal was positioned in the midline of the pre-pubic region. Females were positioned in right lateral recumbency to locate the left ovarian pedicle, and the uterine horn was held by a transcutaneous suture.The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
3
5
0
1
Order By: Relevance
“…Although in a study in bitches [10], and in one with cats [12], reported greater surgical time for haemostasis using suture thread than bipolar electrocoagulation or clips, the mean surgical time in the present study was lower than those reported by these authors. Furthermore, the surgical time from this study is similar to that of other studies in cats in which haemostasis of the OAVC was achieved using bipolar electrocoagulation [5,17,18].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Although in a study in bitches [10], and in one with cats [12], reported greater surgical time for haemostasis using suture thread than bipolar electrocoagulation or clips, the mean surgical time in the present study was lower than those reported by these authors. Furthermore, the surgical time from this study is similar to that of other studies in cats in which haemostasis of the OAVC was achieved using bipolar electrocoagulation [5,17,18].…”
Section: Discussionsupporting
confidence: 74%
“…Although pneumoperitoneum pressure of 10 mmHg has been previously recommended [12,17], the 4 mmHg pressure used in this study enabled excellent visualization and manipulation of the organs, similarly to previous reports [5,7,18]. It is known that the greater the intra-abdominal pressure, the greater the CO 2 absorption by the peritoneum and, consequently, the greater the cardiorespiratory alterations observed [13].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Isso se deve ao avanço tecnológico de instrumentos adequados e modernos, e também maior capacitação técnica dos cirurgiões. Contudo, algumas alterações fisiológicas deletérias podem ocorrer devido a necessidade de criação de um espaço intra-abdominal caracterizado pelo pneumoperitônio (FERREIRA et al, 2013;TAVARES et al, 2016).…”
Section: Desenvolvimento Da Ovariohisterecomia Videolaparoscópica E Eunclassified